The effect of becoming a Fistula Advocate on the recovery of women with Obstetric Fistula in Sierra Leone: A qualitative study - Zoë Vowles; Regina Bash-Taqi; Alusine Kamara; Mabel Kuteh; Sergio A. Silverio; Ibrahim Turay; Stephen Peckham (Public Library of Science (PLoS), 2023)
Engaging women affected by Obstetric Fistula as advocates has been proposed as an effective strategy to raise awareness of the condition. Limited literature exists on the experience of those who become advocates. A model of community education, in Sierra Leone, trained women affected by Obstetric Fistula to become volunteer Fistula Advocates. This study explored Advocates' perception of their role and its influence on their recovery and reintegration. This was a qualitative study, undertaken in Sierra Leone, collecting data from 7 Fistula Advocates and 3 Key Informants (with roles in either clinical or outreach care for women with Obstetric Fistula or training and supervision of Advocates), using semi-structured interviews. Data was subject to a thematic analysis and related to a conceptual framework for mental health recovery. Intrinsic factors motivating Advocates to undertake this role were influenced by psycho-social support received and the possibility for financial independence. Advocates used personal stories in their work to define a new identity, change perceptions and reduce stigma. Benefits associated with the interactions and relationships created through providing and receiving peer support were voiced. Surgical treatment was described as an important factor influencing recovery. The Advocates said economic empowerment helped recovery and reintegration, and the voluntary nature of the Advocate role limited the impact of this. Overall Advocates perceived their role positively, reporting psychological, social, and economic benefits. The complexities of recovery from Obstetric Fistula were highlighted and connections drawn between the treatment of physical symptoms, the socio-cultural context and mental health recovery. They described the role positively influencing existing relationships and initiating supportive, empowering social interactions between women affected by Obstetric Fistula and with Non-Governmental Organisation staff and community members. The study offers insights into the potential for community-based approaches to facilitate access to treatment for sensitive and stigmatising health problems and support recovery.